Opening address at the Symposium on Encounters between Religions in Old Nordic Times and on Cultic Place-Names, arranged by the Donner Institute 19-21 August 1987 - Edsman, Carl-Martin (Scripta Instituti Donneriani Aboensis, 1990)
This paper broadly discusses the topics presented at the symposium.